STRATEGI BRANDING PACITAN PARADISE OF JAVA DALAM MEMBANGUN SEKTOR PARIWISATA DI KABUPATEN PACITAN - Septian Poerdiarti; Herru Prasetya Widodo (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract: Pacitan Regency is a border area located on the Southwestern tip of East Java Province, with most of it in the form of hills, mountains and steep ravines. Located in the border region, making Pacitan Regency rich in natural wealth. One of the attractions of Pacitan Regency is the variety of tourism owned. Pacitan Regency with a variety of tourist destinations, is now starting to build and strengthen its image with a branding strategy that is managed by one of the local government agencies, namely the Dinas Pariwisata, Kepemudaan dan Olahraga or commonly abbreviated as Disparpora. The purpose of this study is to know and learn branding strategies and constraints to building the tourism sector in Pacitan Regency. This study uses qualitative methods, with the type of data that is owned namely primary data and secondary data. Data collected through interviews and documentation, which is then tested for validity using triangulation techniques to examine the same data, but with a different technique, and using analytical techniques that include data reduction, data display, and conclusion. The results of this study found the use of Pacitan Paradise of Java as a brand identity, supported by various promotional activities. In addition to promotion, various supporting potentials such as the potential of the society and the physical conditions of tourist destinations are also built to strengthen branding. Constraints on branding strategies that is carried out lies in problems such as the budget, awareness of the internal and external parties involved, the awareness of the internal and external parties involved, and the location of the Pacitan Regency which is still difficult to access. Keywords: Branding Strategy, Tourism, Pacitan Regency Abstrak: Kabupaten Pacitan merupakan daerah perbatasan yang terletak diujung Barat Daya dari Provinsi Jawa Timur, dengan sebagian besar berupa bukit, gunung dan jurang terjal. Terletak diwilayah perbatasan, menjadikan Kabupaten Pacitan berlimpah kekayaan alam. Salah satu daya tarik dari Kabupaten Pacitan adalah beragam pariwisata yang dimiliki. Kabupaten Pacitan dengan beragam destinasi wisata, kini mulai membangun dan mengukuhkan image dengan strategi branding yang dikelola oleh salah satu instansi pemerintah daerah yaitu Dinas Pariwisata, Kepemudaan dan Olahraga atau yang biasa disingkat Disparpora. Tujuan penelitian ini untuk mengetahui dan mempelajari strategi branding serta hambatan-hambatan untuk membangun sektor pariwisata di Kabupaten Pacitan. Penelitian ini menggunakan metode kualitatif, dengan jenis data yang dimiliki yaitu data primer dan data sekunder. Pengambilan data dilakukan melalui wawancara dan dokumentasi, yang kemudian diuji keabsahaannya menggunakan triangulasi teknik dengan mengecek data yang sama, namun dengan teknik yang berbeda, serta penggunaan teknik analisa yang meliputi reduksi data, tampilan data dan penarikan kesimpulan. Hasil penelitian ini menemukan penggunaan Pacitan Paradise of Java sebagai identitas brand, yang didukung dengan berbagai kegiatan promosi. Selain promosi, berbagai potensi pendukung seperti potensi masyarakat dan kondisi fisik dari destinasi wisata turut dibangun untuk menguatkan branding. Hambatan pada strategi branding yang dilakukan terletak pada masalah seperti anggaran, kesadaran pihak intenal dan eksternal yang terlibat, serta lokasi Kabupaten Pacitan yang masih sulit untuk diakses. Kata Kunci: Strategi Branding, Pariwisata, Kabupaten Pacitan